L’éloge du “régime mesuré” et la cuisine du pouvoir chez Xénophon - Pontier, Pierre (Food & History, 2015)
Abstract The aim of this paper is to elucidate the meaning of Xenophon’s idea of a “moderate diet”. This expression must not be reduced to the consumption of food; it also encompasses more general living conditions. Whatever diet Xenophon conceives (Spartan, Persian, and Socratic) they are all characterized by their sobriety and are all linked to the political ideas of the historian himself. The praise of a “moderate diet” goes along with his criticism of the search for culinary pleasure (hêdupatheia) and for sophisticated food. Abstract Cette étude essaie de faire le point sur ce que Xénophon entend par “régime mesuré” ; le terme doit se comprendre au sens large de régime de vie et pas uniquement de régime alimentaire. Qu’il soit perse, spartiate ou socratique, le régime idéal de Xénophon se caractérise par sa sobriété et par son interaction avec les idéaux politiques de l’historien. L’éloge du régime mesuré s’accompagne logiquement de la critique de la pure recherche du plaisir alimentaire (hèdupatheia) et de la sophistication des aliments.